The Dietary Intakes of Calcium and Bone Health Related Nutrients Among Individuals with and without Spinal Cord Injury - Miyatani, Masae; Craven, B. Cathy; Loewenberger, Eva; McGillivray, Colleen F.; Adachi, Jonathan D. (Journal of Nutritional Therapeutics, 2014)
Objectives: The purposes of this observational study were to: 1) describe and compare the intakes of nutrients related to bone health among a group of individuals with traumatic spinal cord injury (SCI) versus a group of age, gender and weight matched non–SCI peers; and 2) contrast the participant’s nutrient intakes against current dietary reference intakes (DRIs). Methods: Consenting participants included: 87 individuals with SCI (C2-T10 AIS A-D) aged 18-68 years and 85 non-SCI individuals. Participants’ nutrient intakes were determined using a 24-hour dietary recall. Participants were grouped by gender, age (19-30yrs, 31-50yrs, 51-68yrs), and impairment (SCI and non-SCI). Additionally, the nutrient intakes were contrasted with the DRIs parameters. Results: The range for mean calcium intakes across all age strata was 870-1087mg/day for SCI men and 848-1087mg/day for SCI women. The range for mean calcium intakes of the non-SCI participants were similar (men: 900-909mg/day; women: 796-1160mg/day). The majority of SCI and non-SCI men (64 - 86% of participants) in all age groups and SCI and non-SCI women in the 52-68 yrs group (72 and 73% of participants) did not meet the DRIs recommendation for calcium. Additionally many participants did not meet the DRIs recommendation for magnesium (38-55%) and potassium (71-95%) regardless of gender and impairment. The majority (60-70%) of participants consumed excessive amounts of sodium with the exception of non-SCI women. Conclusions: Dietary calcium intakes among SCI and non-SCI participants were not significantly different from each other. However, the dietary calcium intakes of both impairment groups were less than the recommended DRIs; SCI men and women are a target for nutritional interventions based on their calcium, magnesium potassium and sodium intakes.